DAMPAK PEMBERIAN NIASIN DAN KRONIUM TERHADAP PROFIL DISLIPID PADA PENDERITA DISLIPIDEMIA - A. Murdiana D.; Almasyhuri Almasyhuri; Reviana Reviana; Martuti S.; Enok Yuhajah; Muhilal Muhilal (Persagi, 1998)
A study on niacin and chromium supplementation has been conducted to women of 30-60 years old with cholesterol level between 200-250 mg/dl. The aimed of the study was to see the effect of the supplementation on blood cholesterol, triglyceride and low density lipoprotein (LDL). Fourty two respondents were selected purposively and divided into 4 groups. The supplementation was in the form of capsules and given for 3 weeks. Group I, 10 respondents received 200 mcg of chromium; Group II, 7 respondents received chromium 200 mcg and niacin 2x75 mg; Group III, 12 respondents received 2x75 mg niacin and Group IV, 13 respondents received 2x75 mg fructose as placebo. Data collected including anthrophometric, dietary recall for 1x24 hours and clinical status. Analysis of blood sample for cholesterol and triglyceride was done using enzymatic calorimetric method (CHOD-PAP) whereas LDL was done using PVS method (GPO-PAP). The results of this study showed that niacin supplementation significantly decreased cholesterol and LDL level by 15% and 13% respectively, chromium supplementation significantly decreased cholesterol and LDL level by 15% and 20% respectively. Cholesterol and LDL remained in that level three weeks afterwards. The mixture of niacin and chromium supplementation significantly decreased only cholesterol level by 10%. Triglyceride level decreased in all groups including placebo group but not statistically significant. Keywords: supplementtaion, niacin, cromium, cholsterol, triglyceride, low density lipoprotein.